(untitled) (Research, Society and Development, 2021)
Classified as a pandemic by the World Health Organization, COVID-19 has become a protagonist in public health demands around the world. In Brazil, the second country with the most deaths, Rio Grande do Sul is the sixth state most affected by COVID-19. Therefore, an online research was conducted with the residents of the city of Rio Grande, in the south of the state, to assess the impact of the pandemic on the local population in relation to behavioral habits of different groups. Through an online questionnaire, it was possible to collect data from 1188 individuals and to support a quantitative and descriptive study about the behavioral changes of the rio-grandinos in relation to COVID-19. The results showed that although men were the ones who changed the most behavioral habits with the arrival of the pandemic - such as frequent hand washing - women were the ones who had the highest percentages of social distance and had the highest concerns about being infected. This behavioral trend is reflected in the city’s epidemiological data, in which women were in the minority in relation to the number of cases and also the number of deaths in the city. Factors such as family income and schooling influence the behavior of rio-grandinos in relation to habits during the pandemic. As such, the study and understanding of practices adopted by the population is fundamental to improve preventive campaigns and there is a readjustment in the dialogue with the population to improve measures to contain the pandemic.